Carcinoma hepatico colangiocelular en ocas sometidas a crianza intensiva - Menendez, I.=700 1 Merino, N.
(Es, En)
Ilus., 7 ref.
Keywords: PATO; ENFERMEDADES HEPATICAS; CARCINOMA; HEPATITIS; NEOPLASMAS; CUBA; OCAS; CARCINOMA HEPATICO; HETOPATIAS